A vanadium flow battery electrolyte containing a composite additive, and a preparation method and application thereof

CN123018041APending Publication Date: 2026-10-30RIGHTFUL TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611320666.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-28
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0009]为针对现有全钒液流电池电解液高温易沉淀、低温易析晶、温域适配范围窄、循环容量衰减快、电化学极化阻抗大等技术缺陷,本发明提供一种含复合添加剂的全钒液流电池电解液及其制备方法和应用

Benefits of technology

[0037]本发明将有机膦酸可逆螯合稳化技术与氨基磺酸改性稀土静电分散技术结合,此双组分分别针对性解决高温沉淀、低温析晶、电极极化、循环衰减等核心问题,机理耦合性强、性能互补性高,克服了现有技术无法兼顾高低温稳定性、电化学效率与循环寿命的技术缺陷。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123018041A_ABST
    Figure CN123018041A_ABST
Patent Text Reader

Abstract

The application provides a vanadium redox flow battery electrolyte containing a composite additive and a preparation method and application thereof, the electrolyte comprising a basic vanadium electrolyte and a composite additive; wherein the composite additive accounts for 0.8% to 2.5% of the total mass of the basic vanadium electrolyte; the composite additive is composed of hydroxyethylidene diphosphonic acid and lanthanum chloride modified by amino sulfonic acid, and the mass ratio of the hydroxyethylidene diphosphonic acid to the amino sulfonic acid modified lanthanum chloride is (3-5):1. The application reduces the side reaction activity of rare earth ions by surface modification of amino sulfonic acid and grafting of a sulfonic acid polar functional group on the surface of lanthanum ions, avoids electrode adsorption polarization problems, and at the same time, the modified lanthanum ions have an electrostatic shielding effect, which can neutralize the excess charge on the surface of vanadium ions, weaken the electrostatic agglomeration force between vanadium ions, reduce the crystallization precipitation trend of vanadium salt, and improve the low-temperature solubility of low-valence vanadium ions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of vanadium redox flow battery technology, and in particular to a full vanadium redox flow battery electrolyte containing composite additives, its preparation method, and its application. Background Technology

[0002] The working principle of a vanadium redox flow battery relies on the reversible redox reaction of multivalent vanadium ions to achieve energy storage and release. The core components of the system include positive and negative electrolytes, ion exchange membranes, bipolar plates, graphite felt electrodes, a storage tank, and a circulation control system. The electrolyte is the only active energy carrier, accounting for more than 40% of the overall battery cost, and its performance directly determines the overall battery performance. Currently, commercially available vanadium redox flow batteries generally use concentrated sulfuric acid as the supporting electrolyte and multivalent vanadium ions as the active material, forming a sulfuric acid-vanadium ion homogeneous system. While this system has readily available raw materials, mature technology, and controllable costs, it suffers from several inherent technical defects in industrial applications involving long-term outdoor extreme temperatures, high-rate charge-discharge cycles, and long-cycle periods, severely hindering the large-scale widespread adoption of vanadium redox flow batteries.

[0003] The core defects of traditional sulfuric acid-based vanadium electrolytes are concentrated in four aspects: easy precipitation and instability under high temperature conditions, easy crystallization and failure under low temperature conditions, valence imbalance during long-term cycling, large electrochemical polarization impedance, and low energy efficiency.

[0004] Firstly, high-temperature environments trigger the hydrolysis, polymerization, and precipitation of pentavalent vanadium, resulting in permanent loss of active materials. When the ambient temperature exceeds 45°C, the chemical stability of pentavalent vanadium ions in traditional electrolytes decreases significantly. Hydrated vanadium ions in high-concentration sulfuric acid systems are prone to dehydroxylation polymerization, gradually forming soluble oligovanadates, which further aggregate to form insoluble vanadium pentoxide microcrystalline precipitates. These precipitates lack electrochemical activity and cannot participate in charge-discharge redox reactions. This not only directly causes a decrease in the effective vanadium concentration of the electrolyte and a significant drop in battery capacity, but also clogs electrode micropores, ion exchange membrane channels, and circulation pipelines, leading to increased system pipeline pressure drop, poor electrolyte circulation, and localized overheating of equipment, significantly increasing the operation and maintenance costs of energy storage power stations.

[0005] Secondly, the low-temperature environment causes a sharp drop in the solubility of vanadium salts, leading to crystallization and blockage, which in turn causes battery failure. The stable low-temperature critical temperature of traditional vanadium electrolytes is about 0°C. Under low-temperature conditions, the solubility of divalent and trivalent low-valence vanadium salts decreases significantly, making it easy to precipitate needle-like and plate-like vanadium salt crystals. Vanadium salt crystallization directly causes a surge in electrolyte viscosity, a decrease in ion migration rate, and a reduction in conductivity, exacerbating battery charge-discharge polarization and significantly reducing voltage efficiency. At the same time, the precipitated crystals can easily wear down the circulation pump, block pipelines and membrane modules, increase electrolyte circulation resistance, and increase system operating energy consumption.

[0006] Third, under long-term cyclic conditions, vanadium ion valence state imbalance is severe, leading to numerous side reactions and rapid capacity decay. During long-term charge-discharge cycles of vanadium redox flow batteries, the electrolyte undergoes a series of irreversible side reactions, including ion transmembrane permeation, concentration diffusion, oxidation of low-valence vanadium, and vanadium ion disproportionation. This causes the vanadium ion valence state ratio in the positive and negative electrode electrolytes to deviate from the optimal equilibrium state, resulting in a continuous decrease in the utilization rate of active materials. Simultaneously, divalent and trivalent low-valence vanadium ions have weak oxidation resistance and are easily oxidized and deactivated by oxygen in the air, further exacerbating electrolyte performance degradation. After 1000 cycles, conventional unmodified electrolytes retain only 75%–80% of their capacity, which is insufficient to meet the engineering requirements of energy storage power stations for stable operation over a long period of more than 20 years. Fourth, the electrolyte has high polarization resistance, resulting in low energy utilization efficiency.

[0007] To address these issues, existing technologies often employ modification methods such as single organic additives, single inorganic metal ion doping, or simple system optimization. However, the modification effects are significantly limited. Single alcohol, carboxylic acid, and common phosphonic acid organic additives can only slightly improve the solubility of vanadium ions and optimize low-temperature crystallization performance, but they cannot suppress the polymerization and precipitation behavior of pentavalent vanadium at high temperatures, resulting in limited improvement in high-temperature stability. Inorganic additives such as magnesium ions, aluminum ions, and common rare earth ions can alleviate the high-temperature precipitation problem to some extent, but inorganic ions are prone to adsorption and enrichment on the electrode surface, inducing electrochemical side reactions, increasing charge transfer impedance, reducing battery energy efficiency, and failing to form stable complex structures with vanadium ions, thus offering almost no improvement in low-temperature anti-crystallization performance.

[0008] In summary, current vanadium electrolyte modification technologies generally suffer from technical pain points such as single function, poor synergy, difficulty in achieving both high and low temperature stability, and inability to simultaneously improve efficiency and lifespan. There is an urgent need to develop a novel composite modified electrolyte system with a molecular-level synergistic modification mechanism that can simultaneously achieve high-temperature anti-precipitation, low-temperature anti-crystallization, low polarization, long cycle life, and wide temperature adaptability. Summary of the Invention

[0009] To address the technical shortcomings of existing vanadium redox flow battery electrolytes, such as easy precipitation at high temperatures, easy crystallization at low temperatures, narrow temperature range adaptability, rapid capacity decay during cycles, and high electrochemical polarization impedance, this invention provides a vanadium redox flow battery electrolyte containing composite additives, its preparation method, and its application.

[0010] To achieve the above-mentioned objectives, the present invention provides the following technical solution:

[0011] A vanadium redox flow battery electrolyte containing composite additives, characterized in that it comprises a basic vanadium electrolyte and composite additives;

[0012] The composite additive accounts for 0.8% to 2.5% of the total mass of the base vanadium electrolyte; the composite additive is composed of hydroxyethylidene diphosphonic acid and aminosulfonic acid-modified lanthanum chloride, and the mass ratio of hydroxyethylidene diphosphonic acid to aminosulfonic acid-modified lanthanum chloride is (3~5):1.

[0013] In some embodiments, the base vanadium electrolyte in the vanadium redox flow battery containing composite additives is a sulfuric acid system electrolyte with a total vanadium ion concentration of 1.6~2.2 mol / L and a sulfuric acid concentration of 2.5~3.5 mol / L.

[0014] In some embodiments, in the vanadium redox flow battery electrolyte containing composite additives, the composite additives account for 1.2% to 2.0% of the total mass of the base vanadium electrolyte, and the mass ratio of hydroxyethylidene diphosphonic acid to aminosulfonic acid-modified lanthanum chloride is 4:1.

[0015] In some embodiments, the preparation method of the aminosulfonic acid modified lanthanum chloride in the vanadium redox flow battery electrolyte containing composite additives includes: dissolving the anhydrous lanthanum chloride and the aminosulfonic acid in deionized water at a mass ratio of 1:2.5~3.5, and stirring and reacting at 40~50°C for 2~3 hours.

[0016] In some embodiments, the anhydrous lanthanum chloride in the vanadium redox flow battery electrolyte containing composite additives is vacuum dried before use to remove moisture-absorbing and hydrolyzed impurities.

[0017] The pH of the system is controlled at 3.0~5.0 during the reaction process.

[0018] This invention also provides a method for preparing a vanadium redox flow battery electrolyte containing composite additives as described above, specifically including the following steps:

[0019] S1. Dissolve the anhydrous lanthanum chloride and the aminosulfonic acid in deionized water, modify by constant temperature stirring, concentrate, dry and grind to prepare aminosulfonic acid modified lanthanum chloride powder.

[0020] S2. The hydroxyethylidene diphosphonic acid and the aminosulfonic acid-modified lanthanum chloride powder are stirred evenly to prepare a binary composite additive.

[0021] S3. Take the basic vanadium electrolyte of the sulfuric acid system and pretreat it by stirring at room temperature;

[0022] S4. Add the composite additive to the base vanadium electrolyte, stir and disperse, then heat to 55~65℃ and stir for 2~3 hours to carry out molecular-level complexation modification, and obtain the all-vanadium redox flow battery electrolyte containing the composite additive.

[0023] In some embodiments, the preparation method of the vanadium redox flow battery electrolyte with the composite additive further includes one or more of the following operations after the multi-stage complexation modification: natural cooling, static defoaming, and microporous filtration for impurity removal.

[0024] In some embodiments, in the method for preparing the vanadium redox flow battery electrolyte with composite additives, step S1 satisfies at least one of the following conditions:

[0025] The anhydrous lanthanum chloride and the aminosulfonic acid are dissolved in deionized water at a mass ratio of 1:2.5~3.5, and the constant temperature is 40~50℃;

[0026] The stirring reaction takes 2-3 hours.

[0027] In some embodiments, in the method for preparing the vanadium redox flow battery electrolyte with composite additives, step S4 satisfies at least one of the following conditions:

[0028] The stirring speed is 300~500 r / min.

[0029] The reaction temperature is 55~70℃.

[0030] The reaction time is 2-4 hours;

[0031] The reaction was carried out under isothermal conditions.

[0032] The present invention also provides an application of the vanadium redox flow battery electrolyte containing composite additives as described above in large-scale energy storage vanadium redox flow batteries, which can be applied to wind power energy storage, photovoltaic energy storage, grid peak shaving, distributed energy storage and outdoor energy storage battery systems in high-altitude and cold regions.

[0033] This invention discovered that hydroxyethylidene bisphosphonic acid (HEDP) plays a role in high-temperature anti-precipitation stabilization. The bisphosphonic acid group and hydroxyl active site of the HEDP molecule can react with V in high-concentration vanadium sulfate systems. 4+ V 5+ High-valence vanadium ions undergo specific chelation to form a structurally stable five-membered ring chelate. This chelate structure can encapsulate the vanadium ion hydration shell, preventing collisions and aggregation between vanadium ions. This inhibits the hydrolysis and dehydroxylation polymerization reaction of vanadium ions at high temperatures at the molecular level, improves the irreversible precipitation of vanadium pentoxide, and fundamentally solves the problems of electrolyte instability at high temperatures and loss of active materials.

[0034] This invention modifies the surface of lanthanum ions with aminosulfonic acid, grafting sulfonic acid polar functional groups onto the surface of lanthanum ions. This effectively reduces the side reaction activity of rare earth ions and avoids electrode adsorption polarization problems. At the same time, the electrostatic shielding effect of the modified lanthanum ions can neutralize the excess charge on the surface of vanadium ions, weaken the electrostatic aggregation force between vanadium ions, reduce the tendency of vanadium salt crystallization, and significantly improve the low-temperature solubility of low-valence vanadium ions, thus solving the defects of low-temperature crystallization and viscosity surge.

[0035] This invention discovered that the two components exhibit a significant synergistic effect with no system antagonism. The chelating structure of organophosphonic acid can assist in the uniform dispersion of modified rare earth ions, preventing their aggregation; the electrostatic dispersion effect of modified rare earth ions can promote the uniform distribution of vanadium ions, improving the uniformity and stability of the HEDP chelation reaction.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] This invention combines reversible chelation stabilization technology of organophosphonic acid with rare earth electrostatic dispersion technology modified with aminosulfonic acid. This dual-component approach addresses key issues such as high-temperature precipitation, low-temperature crystallization, electrode polarization, and cycle decay. It exhibits strong mechanistic coupling and high performance complementarity, overcoming the technical shortcomings of existing technologies that cannot simultaneously achieve high and low temperature stability, electrochemical efficiency, and cycle life.

[0038] This invention, through precise component ratios and surface structure modification, expands the stable operating temperature range of the electrolyte from the traditional 0℃~45℃ to -20℃~60℃. After standing at 60℃ for 72 hours, no precipitation, stratification, or turbidity occurs, and the vanadium ion concentration decay rate is less than 1.2%. After standing at -20℃ for 24 hours, no vanadium salt crystals precipitate, and the electrolyte viscosity and conductivity remain essentially stable. It is suitable for extreme outdoor conditions in various parts of my country, including high temperatures, extreme cold, and high altitudes, and its application scenarios far exceed those of existing conventional modified electrolytes.

[0039] The composite additive of this invention can effectively stabilize the balance of multivalent vanadium ions, inhibit the oxidation and deactivation of low-valent vanadium ions, alleviate the imbalance of vanadium ion transmembrane permeation, and significantly reduce various side reactions during charge and discharge. After 1000 consecutive charge-discharge cycle tests, the battery capacity retention rate corresponding to the modified electrolyte can reach over 92%, which is more than 15% higher than the 75%~80% capacity retention rate of traditional electrolytes. The electrolyte system remains stable during long-term cycling without precipitation or blockage, significantly extending the equipment maintenance cycle and significantly reducing the total life-cycle cost of the battery.

[0040] The modified system of this invention optimizes the electrolyte ion transport environment, reduces the transport resistance of the vanadium ion solvation layer, lowers the charge transfer impedance at the electrode interface, and improves the redox reaction rate and reversibility of vanadium ions. After modification, the battery energy efficiency remains stable at 82%~85%, reducing energy loss during charging and discharging in the energy storage system and improving the utilization rate of new energy sources and the economic benefits of energy storage power stations. Attached Figure Description

[0041] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.

[0042] Figure 1 This is a comparison chart showing the decrease in vanadium ion concentration between the examples and the comparative examples;

[0043] Figure 2 This is a comparison chart showing the electrolyte viscosity of the examples and comparative examples;

[0044] Figure 3 The graphs show the average energy efficiency test results for the examples and comparative examples;

[0045] Figure 4 The graphs show the long-cycle capacity retention test results for both the example and comparative models. Detailed Implementation

[0046] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0047] Unless otherwise specified, the raw materials used in the embodiments of the present invention are all purchased commercially and used directly without any special treatment.

[0048] Unless otherwise specified, the analytical methods in the embodiments all adopt conventional instrument or equipment settings and conventional analytical methods.

[0049] Example 1

[0050] A vanadium redox flow battery electrolyte containing composite additives is composed of a base electrolyte and composite additives, wherein the amount of composite additives added is 1.5% of the total mass of the base electrolyte; the composite additives are compounded by hydroxyethylidene diphosphonic acid and aminosulfonic acid modified lanthanum chloride in an optimal mass ratio of 4:1.

[0051] Preparation process of aminosulfonic acid modified lanthanum chloride: Anhydrous lanthanum chloride and aminosulfonic acid are dissolved in high-purity deionized water at a mass ratio of 1:3. The surface modification is completed by stirring at 45℃ for 2.5h. The mixture is then concentrated under reduced pressure to remove water, dried under vacuum at 80℃ for 4h, ground, and passed through a 200-mesh sieve to obtain modified powder.

[0052] The electrolyte preparation steps are as follows:

[0053] S1. Prepare aminosulfonic acid modified lanthanum chloride powder according to the above-mentioned preparation process of aminosulfonic acid modified lanthanum chloride, and seal it for later use;

[0054] S2. Weigh hydroxyethylidene diphosphonic acid and modified lanthanum chloride powder at a mass ratio of 4:1, stir and mix evenly at room temperature to prepare a binary composite additive.

[0055] S3. Take a quantitative amount of basic electrolyte and stir magnetically at room temperature for 30 minutes to remove bubbles and suspended impurities;

[0056] S4. Add the composite additive to the base electrolyte in three equal portions, with a 15-minute interval between each addition, and stir at 400 rpm throughout the process. After the addition is complete, stir at a constant temperature of 60°C for 2.5 hours to complete the full complexation modification.

[0057] S5. Allow to cool naturally to room temperature, let stand for 4 hours to defoam, and then filter under negative pressure using a 0.22μm organic filter membrane to obtain the finished modified electrolyte.

[0058] Example 2

[0059] A vanadium redox flow battery electrolyte containing composite additives is provided. The amount of composite additives added is 1.2% of the total mass of the base electrolyte. The mass ratio of hydroxyethylidene diphosphonic acid to modified lanthanum chloride is 4:1. The remaining raw material parameters, powder modification process, and electrolyte preparation steps are completely consistent with those in Example 1. The specific preparation method is as follows:

[0060] A vanadium redox flow battery electrolyte containing composite additives is composed of a base electrolyte and composite additives, wherein the amount of composite additives added is 1.2% of the total mass of the base electrolyte; the composite additives are compounded by hydroxyethylidene diphosphonic acid and aminosulfonic acid modified lanthanum chloride in an optimal mass ratio of 4:1.

[0061] Preparation process of aminosulfonic acid modified lanthanum chloride: Anhydrous lanthanum chloride and aminosulfonic acid are dissolved in high-purity deionized water at a mass ratio of 1:3. The surface modification is completed by stirring at 45℃ for 2.5h. The mixture is then concentrated under reduced pressure to remove water, dried under vacuum at 80℃ for 4h, ground, and passed through a 200-mesh sieve to obtain modified powder.

[0062] The electrolyte preparation steps are as follows:

[0063] S1. Prepare aminosulfonic acid modified lanthanum chloride powder according to the above-mentioned preparation process of aminosulfonic acid modified lanthanum chloride, and seal it for later use;

[0064] S2. Weigh hydroxyethylidene diphosphonic acid and modified lanthanum chloride powder at a mass ratio of 4:1, stir and mix evenly at room temperature to prepare a binary composite additive.

[0065] S3. Take a quantitative amount of basic electrolyte and stir magnetically at room temperature for 30 minutes to remove bubbles and suspended impurities;

[0066] S4. Add the composite additive to the base electrolyte in three equal portions, with a 15-minute interval between each addition, and stir at 400 rpm throughout the process. After the addition is complete, stir at a constant temperature of 60°C for 2.5 hours to complete the full complexation modification.

[0067] S5. Allow to cool naturally to room temperature, let stand for 4 hours to defoam, and then filter under negative pressure using a 0.22μm organic filter membrane to obtain the finished modified electrolyte.

[0068] Example 3

[0069] A vanadium redox flow battery electrolyte containing composite additives is provided. The amount of composite additives added is 2.0% of the total mass of the base electrolyte. The remaining raw material parameters, powder modification process, and electrolyte preparation steps are completely consistent with those in Example 1.

[0070] A vanadium redox flow battery electrolyte containing composite additives is composed of a base electrolyte and composite additives, wherein the amount of composite additives added is 2.0% of the total mass of the base electrolyte; the composite additives are compounded by hydroxyethylidene diphosphonic acid and aminosulfonic acid modified lanthanum chloride in an optimal mass ratio of 4:1.

[0071] Preparation process of aminosulfonic acid modified lanthanum chloride: Anhydrous lanthanum chloride and aminosulfonic acid are dissolved in high-purity deionized water at a mass ratio of 1:3. The surface modification is completed by stirring at 45℃ for 2.5h. The mixture is then concentrated under reduced pressure to remove water, dried under vacuum at 80℃ for 4h, ground, and passed through a 200-mesh sieve to obtain modified powder.

[0072] The electrolyte preparation steps are as follows:

[0073] S1. Prepare aminosulfonic acid modified lanthanum chloride powder according to the above-mentioned preparation process of aminosulfonic acid modified lanthanum chloride, and seal it for later use;

[0074] S2. Weigh hydroxyethylidene diphosphonic acid and modified lanthanum chloride powder at a mass ratio of 4:1, stir and mix evenly at room temperature to prepare a binary composite additive.

[0075] S3. Take a quantitative amount of basic electrolyte and stir magnetically at room temperature for 30 minutes to remove bubbles and suspended impurities;

[0076] S4. Add the composite additive to the base electrolyte in three equal portions, with a 15-minute interval between each addition, and stir at 400 rpm throughout the process. After the addition is complete, stir at a constant temperature of 60°C for 2.5 hours to complete the full complexation modification.

[0077] S5. Allow to cool naturally to room temperature, let stand for 4 hours to defoam, and then filter under negative pressure using a 0.22μm organic filter membrane to obtain the finished modified electrolyte.

[0078] Example 4

[0079] A vanadium redox flow battery electrolyte containing composite additives, wherein the mass ratio of hydroxyethylidene diphosphonic acid to modified lanthanum chloride in the composite additives is 3:1, the amount of composite additives added is 1.5%, and the remaining parameters and preparation process are the same as in Example 1.

[0080] A vanadium redox flow battery electrolyte containing composite additives is composed of a base electrolyte and composite additives, wherein the amount of composite additives added is 1.5% of the total mass of the base electrolyte; the composite additives are compounded by hydroxyethylidene diphosphonic acid and aminosulfonic acid modified lanthanum chloride in an optimal mass ratio of 3:1.

[0081] Preparation process of aminosulfonic acid modified lanthanum chloride: Anhydrous lanthanum chloride and aminosulfonic acid are dissolved in high-purity deionized water at a mass ratio of 1:3. The surface modification is completed by stirring at 45℃ for 2.5h. The mixture is then concentrated under reduced pressure to remove water, dried under vacuum at 80℃ for 4h, ground, and passed through a 200-mesh sieve to obtain modified powder.

[0082] The electrolyte preparation steps are as follows:

[0083] S1. Prepare aminosulfonic acid modified lanthanum chloride powder according to the above-mentioned preparation process of aminosulfonic acid modified lanthanum chloride, and seal it for later use;

[0084] S2. Weigh hydroxyethylidene diphosphonic acid and modified lanthanum chloride powder at a mass ratio of 4:1, stir and mix evenly at room temperature to prepare a binary composite additive.

[0085] S3. Take a quantitative amount of basic electrolyte and stir magnetically at room temperature for 30 minutes to remove bubbles and suspended impurities;

[0086] S4. Add the composite additive to the base electrolyte in three equal portions, with a 15-minute interval between each addition, and stir at 400 rpm throughout the process. After the addition is complete, stir at a constant temperature of 60°C for 2.5 hours to complete the full complexation modification.

[0087] S5. Allow to cool naturally to room temperature, let stand for 4 hours to defoam, and then filter under negative pressure using a 0.22μm organic filter membrane to obtain the finished modified electrolyte.

[0088] Example 5

[0089] A vanadium redox flow battery electrolyte containing composite additives, wherein the mass ratio of hydroxyethylidene diphosphonic acid to modified lanthanum chloride in the composite additives is 5:1, the amount of composite additives added is 1.5%, and the remaining parameters and preparation process are the same as in Example 1.

[0090] A vanadium redox flow battery electrolyte containing composite additives is composed of a base electrolyte and composite additives, wherein the amount of composite additives added is 1.5% of the total mass of the base electrolyte; the composite additives are compounded by hydroxyethylidene diphosphonic acid and aminosulfonic acid modified lanthanum chloride in an optimal mass ratio of 5:1.

[0091] Preparation process of aminosulfonic acid modified lanthanum chloride: Anhydrous lanthanum chloride and aminosulfonic acid are dissolved in high-purity deionized water at a mass ratio of 1:3. The surface modification is completed by stirring at 45℃ for 2.5h. The mixture is then concentrated under reduced pressure to remove water, dried under vacuum at 80℃ for 4h, ground, and passed through a 200-mesh sieve to obtain modified powder.

[0092] The electrolyte preparation steps are as follows:

[0093] S1. Prepare aminosulfonic acid modified lanthanum chloride powder according to the above-mentioned preparation process of aminosulfonic acid modified lanthanum chloride, and seal it for later use;

[0094] S2. Weigh hydroxyethylidene diphosphonic acid and modified lanthanum chloride powder at a mass ratio of 4:1, stir and mix evenly at room temperature to prepare a binary composite additive.

[0095] S3. Take a quantitative amount of basic electrolyte and stir magnetically at room temperature for 30 minutes to remove bubbles and suspended impurities;

[0096] S4. Add the composite additive to the base electrolyte in three equal portions, with a 15-minute interval between each addition, and stir at 400 rpm throughout the process. After the addition is complete, stir at a constant temperature of 60°C for 2.5 hours to complete the full complexation modification.

[0097] S5. Allow to cool naturally to room temperature, let stand for 4 hours to defoam, and then filter under negative pressure using a 0.22μm organic filter membrane to obtain the finished modified electrolyte.

[0098] Comparative Example 1

[0099] The traditional pure sulfuric acid system vanadium-containing electrolyte, without any additives, has a total vanadium ion concentration of 2.0 mol / L and a sulfuric acid concentration of 3.0 mol / L, and is currently the mainstream commercial electrolyte system.

[0100] Comparative Example 2

[0101] A single additive consisting of 1.5% by mass of hydroxyethylidene diphosphonic acid was added, without any modified rare earth components. The preparation method and electrolyte parameters were the same as in Example 1.

[0102] Comparative Example 3

[0103] Only 1.5% by mass of unmodified pure lanthanum chloride powder was added, without any organophosphonic acid components. The preparation method and electrolyte parameters were the same as in Example 1.

[0104] Comparative Example 4

[0105] The preparation method and electrolyte parameters are the same as in Example 1, using a simple physical compounding of common lanthanum chloride and hydroxyethylidene diphosphonic acid at a ratio of 4:1, without aminosulfonic acid surface modification process, and the total amount of composite additives added is 1.5%.

[0106] Example 1

[0107] Performance testing experiments and results analysis

[0108] Test conditions and standards

[0109] Test cell: 5cm×5cm standard vanadium redox flow battery single module; Ion exchange membrane: Nafion212 membrane; Electrode: graphite felt electrode; Charge / discharge regime: current density 80mA / cm², charging cut-off voltage 1.7V, discharging cut-off voltage 0.8V; High temperature test: 60℃ constant temperature sealed standing for 72h; Low temperature test: -20℃ constant temperature sealed standing for 24h; Cyclic test: 1000 continuous charge / discharge cycles at room temperature.

[0110] Performance test results and detailed analysis

[0111] High-temperature thermal stability test (60℃ / 72h)

[0112] Depend on Figure 1 It can be seen that the systems of Examples 1 to 5 have good uniformity; the vanadium ion concentration decay rate is less than 1.2%, and the decay rate of Example 1 is only 0.8%, which shows the best high-temperature stabilization effect.

[0113] The attenuation rate of the system in this invention was 0.8%, a reduction of approximately 90.7% compared to the blank control (8.6%). After standing at high temperature, the system was clear and transparent with no precipitation or stratification, indicating almost no loss of active material. HEDP (Comparative Example 2, 8.1%) showed almost no difference from the blank system (8.6%), proving that organophosphonic acid alone cannot effectively inhibit the hydrolysis, polymerization, and precipitation of pentavalent vanadium at high temperatures. This aligns with the prior art's assessment that single organic additives have limited high-temperature stabilization effects. Unmodified lanthanum chloride (Comparative Example 3, 4.5%) had some high-temperature stabilization effect, but rare earth ions easily adsorbed and accumulated on the electrode surface, inducing electrochemical side reactions, and could not improve low-temperature performance. The basic physical compound (Comparative Example 4, 3.2%) was superior to a single component, but far inferior to this invention (0.8%), proving that the effect of this invention is not a simple superposition of the two components, but rather a molecular-level synergistic effect of good surface modification of aminosulfonic acid and chelation of HEDP.

[0114] Example 2

[0115] Low-temperature anti-crystallization stability test (-20℃ / 24h)

[0116] Depend on Figure 2It can be seen that, after being allowed to stand at low temperature, the electrolytes of all embodiments of the present invention do not exhibit crystal precipitation, stratification, or significant viscosity fluctuations. The electrolytes have good fluidity and light transmittance, and excellent low-temperature adaptability. Among them, the electrolyte viscosity change rate of Example 1 is less than 3%, and the low-temperature stabilization effect is the best.

[0117] Comparative Example 1 (blank electrolyte) and Comparative Example 3 (pure lanthanum chloride electrolyte) showed viscous solidification with a viscosity increase of over 40%, making normal operation impossible. Comparative Example 2 showed an 18% increase in viscosity and significant deterioration in low-temperature performance. Comparative Example 4 (ordinary compound system) showed slight crystallization and a 12% increase in viscosity, indicating poor low-temperature modification effect.

[0118] Example 3

[0119] The long-cycle capacity retention and energy efficiency test (1000 cycles) is shown in Table 1.

[0120] Table 1

[0121]

[0122] From Table 1 and Figure 3 , Figure 4 Cyclic test results demonstrate that the binary synergistic modification system of the present invention, with an optimal ratio of 4:1 and an optimal addition amount of 1.5%, can maximize the improvement of electrolyte cycle stability and electrochemical efficiency. The synergistic effect of the two components is significant, and its performance is far superior to that of single additives and ordinary compound systems, which can ensure the long-term efficient and stable operation of the battery.

[0123] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A vanadium redox flow battery electrolyte containing composite additives, characterized in that, Includes basic vanadium electrolyte and composite additives; The composite additive accounts for 0.8% to 2.5% of the total mass of the base vanadium electrolyte; the composite additive is composed of hydroxyethylidene diphosphonic acid and aminosulfonic acid-modified lanthanum chloride, and the mass ratio of hydroxyethylidene diphosphonic acid to aminosulfonic acid-modified lanthanum chloride is (3~5):

1.

2. The vanadium redox flow battery electrolyte containing composite additives as described in claim 1, characterized in that, The basic vanadium electrolyte is a sulfuric acid system electrolyte with a total vanadium ion concentration of 1.6~2.2 mol / L and a sulfuric acid concentration of 2.5~3.5 mol / L.

3. The vanadium redox flow battery electrolyte containing composite additives as described in claim 1, characterized in that, The composite additive accounts for 1.2% to 2.0% of the total mass of the base vanadium electrolyte, and the mass ratio of hydroxyethylidene diphosphonic acid to aminosulfonic acid-modified lanthanum chloride is 4:

1.

4. The vanadium redox flow battery electrolyte containing composite additives according to claim 1, characterized in that, The preparation method of the aminosulfonic acid modified lanthanum chloride includes: dissolving the anhydrous lanthanum chloride and the aminosulfonic acid in deionized water at a mass ratio of 1:2.5~3.5, and stirring the mixture at 40~50℃ for 2~3 hours.

5. The vanadium redox flow battery electrolyte containing composite additives as described in claim 4, characterized in that, The anhydrous lanthanum chloride is first vacuum dried to remove moisture-absorbing and hydrolyzed impurities before use. The pH of the system is controlled at 3.0~5.0 during the reaction process.

6. A method for preparing a vanadium redox flow battery electrolyte containing composite additives as described in any one of claims 1 to 5, characterized in that, Includes the following steps: S1. Dissolve the anhydrous lanthanum chloride and the aminosulfonic acid in deionized water, modify by constant temperature stirring, concentrate, dry and grind to prepare aminosulfonic acid modified lanthanum chloride powder. S2. The hydroxyethylidene diphosphonic acid and the aminosulfonic acid-modified lanthanum chloride powder are stirred evenly to prepare a binary composite additive. S3. Take the basic vanadium electrolyte of the sulfuric acid system and pretreat it by stirring at room temperature; S4. The composite additive is added to the base vanadium electrolyte, stirred and dispersed, and then heated and stirred to react, and molecular-level complexation modification is carried out to obtain the all-vanadium redox flow battery electrolyte containing the composite additive.

7. The method for preparing the vanadium redox flow battery electrolyte with composite additives as described in claim 6, characterized in that, After completing the multi-stage complexation modification, one or more of the following operations are also included: natural cooling, static defoaming, and microporous filtration for impurity removal.

8. The method for preparing the all-vanadium redox flow battery electrolyte containing composite additives according to claim 6, characterized in that, Step S1 satisfies at least one of the following conditions: The anhydrous lanthanum chloride and the aminosulfonic acid are dissolved in deionized water at a mass ratio of 1:2.5~3.5, and the constant temperature is 40~50℃; The stirring reaction takes 2-3 hours.

9. The method for preparing the all-vanadium redox flow battery electrolyte containing composite additives according to claim 6, characterized in that, Step S4 satisfies at least one of the following conditions: The stirring speed is 300~500 r / min. The reaction temperature is 55~70℃. The reaction time is 2-4 hours.

10. The application of the vanadium redox flow battery electrolyte containing composite additives as described in any one of claims 1 to 5, characterized in that, It is applied to wind power energy storage, photovoltaic energy storage, grid peak shaving, distributed energy storage, and outdoor energy storage battery systems in high-altitude and cold regions.